Permainan Tradisional Riau: Lulu Cina Buta dalam Meningkatkan Keseimbangan Pada Anak Usia Pre-School - S, Putri Wulandini; Kartika, Imelda Rahmayunia; Sartika, Wiwi (Universitas Fort De Kock Bukittinggi, 2023)
Background: Various types of traditional games can be played to improve balance in children. There is a type of traditional game from the people of Riau, namely Lulu Cina Buta, which can improve children's gross motor skills, including balance. This research is to analyze the influence of the traditional game Lulu Cina Buta as a traditional game of the Riau community, to improve balance in pre-school children at Bukittiggi Kindergarten. Methods: This research uses a quasi-experimental design with a two group pre-test post-test with control group approach. The intervention in this research was the traditional game Lulu Cina Buta. The game is played for 30 minutes by the child. The sample used was 50 pre-school children between 4-6 years old in PAUD and Kindergarten in Bukittinggi City, divided into two groups. This research uses a questionnaire research instrument to measure gross motor skills in children, especially balance when children play. The questionnaire used is a balance questionnaire that looks at the child's dynamic balance indicators when walking. There are 3 balance indicators, namely 1 for unbalanced, 2 for less balanced and 3 for balanced. Data analysis used descriptive statistics, dependent t and independent t tests. Results: This research obtained a p-value of 0.008 (p<0.05), so there is effectiveness of this game on children's balance. Conclusion: This game improves children's balance in movement which is the basis for forming children's gross motor skills. It is hoped that through traditional games children can increase their introduction to Indonesian culture which is varied, so that children's gross motor skills can improve optimally and children can get to know more fun traditional Indonesian games.Keywords: Traditional game, Balance, Pre-school